Beyond regionalism? : regional cooperation, regionalism and regionalization in the Middle East / edited by Cilja Harders, Matteo Legrenzi - Harders, Cilja 1968-; Legrenzi, Matteo (The international political economy of new regionalisms series, 2016)
Regional cooperation, regionalism and regionalization in the Middle East are usually considered to be weak and rather ceremonial. However, since September 11, 2001, a new regional order is emerging and the impact of geostrategic changes in the international environment has yet to be satisfactorily studied. With older regional organizations suffering from weaknesses, new forms appear to be developing and flourishing, due either to European support or growing sub-regional identities. This volume offers refined theoretical models and approaches which are attuned to the new dynamics and contradictions of a wide range of regionalist projects in the contemporary Middle East. Case studies of the most important regional organizations in different policy fields offer comprehensive overviews of the main actors, institutions, historical development and current issues.